From Orientation to Advantage: Entrepreneurial and Market Drivers of Indonesian SME Performance - Fitriany, Fitriany (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
Small and medium-sized enterprises (SMEs) dominate Indonesia’s economy, contributing over 60% of GDP and employing nearly the entire labor force, yet many struggle to sustain competitiveness in turbulent markets. This study argues that entrepreneurial and marketing orientations are not mere independent predictors of performance but interdependent postures that channel entrepreneurial drive into market responsiveness and competitive advantage. Using survey data from 233 Indonesian SMEs and analyzed through partial least squares structural equation modeling, the results show that entrepreneurial orientation enhances both marketing orientation and competitive advantage, while marketing orientation directly drives advantage and marketing performance. Competitive advantage, in turn, serves as the critical pathway linking orientations to outcomes. The findings extend resource-based and dynamic capabilities perspectives by situating orientations as upstream enablers of advantage creation. Implications highlight the need for SME owners and policymakers to couple entrepreneurial boldness with market intelligence to achieve sustainable performance.